Globalization and its influence on the governance paradigm of Australian public universities - Christopher, Joseph (Common Ground Publishing LLC, 2011)
This study aims to examine the extent to which globalization has influenced the governance paradigm of Australian public universities. Using a qualitative methodology and analyzing the data against a multi-theoretical governance framework, the findings suggest that the true impact of globalization is dependent on a number of wider influencing forces pertinent to an individual organization. Universities reacted differently to these forces, resulting in different levels of development and implementation of their governance mechanisms and processes. The theoretical implications of the findings support a multi-theoretical approach to governance to facilitate the identification of an organization’s wider influencing forces. The practical implications provide for the identification and incorporation of such forces within an organization’s governance framework to ensure a holistic approach to developing and implementing governance mechanisms and processes. The findings provide avenues for further research with other industry sectors to confirm the above theoretical and practical propositions.